Product strategy and formal structure - Bart, Christopher K. (Strategic Management Journal, 1986)
Abstract This article presents the findings of clinically based research which investigated the relationship between strategy and formal structure at the product level in five diversified consumer packaged goods firms. The findings establish that this relationship is severely constrained. The article also suggests how firms ‘accommodate’ when unable to match organizational structure with product strategy.